2016
DOI: 10.1177/1742395316664959
|View full text |Cite
|
Sign up to set email alerts
|

Living with uncertainty and hope: A qualitative study exploring parents’ experiences of living with childhood multiple sclerosis

Abstract: Background: There is growing recognition that multiple sclerosis (MS) is a possible, albeit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(101 citation statements)
references
References 27 publications
7
94
0
Order By: Relevance
“…Comparable to other literature, the Delphi highlighted the comfort and a sense of purpose that parental caregivers experience when caring for an ill child (Angström-Brännström et al, 2010;Samson et al, 2009). The idea that parents benefited from taking on the role of being an advocate for their child were echoed within literature that described parents feeling in control of their circumstances by being an advocate for their child (Cadell et al, 2012;Hinton & Kirk, 2017;Whiting, 2012).…”
Section: Subprocess Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparable to other literature, the Delphi highlighted the comfort and a sense of purpose that parental caregivers experience when caring for an ill child (Angström-Brännström et al, 2010;Samson et al, 2009). The idea that parents benefited from taking on the role of being an advocate for their child were echoed within literature that described parents feeling in control of their circumstances by being an advocate for their child (Cadell et al, 2012;Hinton & Kirk, 2017;Whiting, 2012).…”
Section: Subprocess Ofmentioning
confidence: 99%
“…Delphi participants agreed that parental caregivers needed access to information that helped them to process and gain control of their situation and other studies have indicated these exact findings (Angström-Brännström et al, 2010;Hinton & Kirk, 2017). In Cadell et al's (2012) mixed-method study of pediatric palliative care parents' personal growth and resources, parents called for a more open process and guidance in finding information for their family.…”
Section: Celebrate Milestonesmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Alternatively, parents have reported benefits to uncertainty, including recognizing that uncertainty allows for the possibility for positive outcomes for their child. 6,9,11,12 This dichotomization of uncertainty appraisals is further elucidated by Mishel's Uncertainty in Illness Theory. Mishel argued that uncertainty is classified as neutral until it has been appraised as either a danger or opportunity.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that uncertainty can negatively affect parental coping and adaptation; and increase feelings of psychological distress, anxiety, depression, and hopelessness . Alternatively, parents have reported benefits to uncertainty, including recognizing that uncertainty allows for the possibility for positive outcomes for their child . This dichotomization of uncertainty appraisals is further elucidated by Mishel’s Uncertainty in Illness Theory.…”
Section: Introductionmentioning
confidence: 99%